A solution-assisted etching preparation of an MOF-derived NH4CoPO4·H2O/Ti3C2Tx MXene nanocomposite for high-performance hybrid supercapacitors. (8th June 2021) - Wei, Wenhui; Luo, Shijian; Zhao, Ying; Li, Xiaoman; Liang, Bin; Fang, Junzhuo; Luo, Min
Abstract : A novel synthetic is explored by introducing the Co-MOF(ZIF-67) into the layer space of Ti3 C2 T x and subsequent in situ etching to transform into NH4 CoPO4 ·H2 O/Ti3 C2 T x nanocomposite and used for high-performance hybrid supercapcitor. Abstract : Hydrated ammonium metal phosphates (AMPs) with numerous electractive sites and intercalated water are the current research focus in the field of supercapacitors. Herein, we have developed a novel approach where Co-MOF(ZIF-67) as a precursor was introduced into the confined space of an MXene layer, and the as-prepared MOF/Ti3 C2 T x was subsequently etched in situ in a solution of (NH4 )2 HPO4 to transform into NH4 CoPO4 ·H2 O nanoparticles with a uniform distribution on the surface of Ti3 C2 T x . NH4 CoPO4 nanoparticles were embedded into MXene nanosheets, while the Ti3 C2 T x MXene endowed AMPs with high electronic conductivity. Benefiting from the synergistic effect of NH4 CoPO4 ·H2 O and MXene, this material showed good rate performance (601 F g −1 at 1.0 A g −1 and 535 F g −1 at 20.0 A g −1 ) and long cycle life (87% capacitance retention up to 5000 cycles at 5 A g −1 ) in a three-electrode system, which can be ascribed to excellent electronic conductivity and short ion transport path. When NH4 CoPO4 ·H2 O/Ti3 C2 T x and activated carbon are used as the positive and negative electrodes of asymmetric supercapacitors (ASCs), the ASC simultaneously shows high energy density (47 W h kg −1 at 1350 W kg −1 ) and power density (18 W h kg −1 at 5000 W kg −1 ), which can be considered as a potential candidate for next-generation energy storage devices.